Novel immediate implantation approach using socket shield with dentin graft. - A/Prof Walid Elamrousy; Professor Mohamed Nassar; demonstrator Moustafa Fayed; lecturer Mohamed Abdelfattah (Elsevier, 2023)
Aim or Purpose: To evaluate the peri-implant clinical and the radiographic changes after immediate implantation in anterior esthetic zone with a novel approach by using socket shield technique alone or combined with autogenous dentin graft that may be used an effective ideal graft substitute. Materials and Methods: Ethical approval of Kafrelsheikh University Research Ethics Committee, and getting written informed consents done for participated 50 patients (20-55 years of both sexes) with anterior teeth indicated for extraction. Patients randomly divided into; Group I underwent immediate implantation using socket shield protocol and group II received the same protocol but the extracted part of the root was reused as a graft substitute in peri-implant gap defect. Clinical parameters [Implant Stability Quotient (ISQ), plaque index and pink aesthetic score (PES)] and radiographic changes using CBCT [to determine horizontal, vertical bone levels and bone density] were recorded at baseline, 6 and 12months. Results: At 6 and 12months; PES, ISQ and bone density in group II were statistically significantly higher than in group I (P<0.001).At 6 and 12months; group I showed a statistically significant loss in horizontal and vertical bone levels compared to group II (P<0.001). Conclusions: Addition of Autogenous dentin graft enhances the peri-implant clinical and the radiographic parameters and could be used an effective ideal graft substitute.As we know, this is the first study using this novel approach in immediate implant placement using socket shield technique combined with autogenous dentin graft.